Molecular pcr assays for detection of Ganoderma pathogenic to oil palm in Malaysia - Nur Hailini Zainol Hilmi; Abu Seman Idris; Mohamed Maizatul-Suriza; Ahmad Zairun Madihah; Ramli Nur-Rashyeda (Penerbit Universiti Kebangsaan Malaysia, 2022)
Ganoderma boninense is a fungal pathogen that causes basal stem rot (BSR) disease in oil palm. Being a serious disease problem to the oil palm industry, monitoring and detecting the pathogen is of the utmost importance to reduce disease spread and facilitate effective management strategies. Because the traditional culture-based assay is time-consuming, labor-intensive, and required special skills in mycology, plant pathologists are turning to more accurate, sensitive, and fast methods such as molecular techniques. In this study, polymerase chain reaction (PCR) assays were developed to detect pathogenic Ganoderma species causing BSR disease in oil palm using a primer designed based on the ribosomal DNA internal transcribed spacer (ITS) region. The effectiveness of conventional and real-time PCR assays was analyzed compared to the traditional isolation-based assay. For artificially inoculated oil palm plantlets, consistent detection of G. boninense was observed. Real-time PCR assay has shown to be more sensitive and rapid in detecting G. boninense in field samples and could potentially serve as a validation tool to other detection techniques for the implementation of effective disease control measures.